1980
DOI: 10.1111/j.1755-3768.1980.tb06683.x
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Hyperosmotic Stress on the Blood‐retinal Barrier Effects on the Electroretinogram

Abstract: Electroretinographic recordings were obtained from cat eyes before and after an intracarotid injection of a hypertonic NaCl-solution. It was found that after the injection the c-wave decreased in amplitude or disappeared, but reappeared within a period of four to six hours, suggesting that there is a reversible opening of the tight junctions following osmotic stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1983
1983
1992
1992

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…This solution is hypertonic, but may not be enough to induce the hypertonic response. Since Tornquist & Ring (1980) reported that the cat c-wave decreased in amplitude or disappeared after an intracarotid injection of hypertonic saline solution (10 ml of 2000 mOsm/kg solution), we conclude that this c-wave enhancement by iodate is not the effect of the osmotic change.…”
Section: Discussionmentioning
confidence: 55%
“…This solution is hypertonic, but may not be enough to induce the hypertonic response. Since Tornquist & Ring (1980) reported that the cat c-wave decreased in amplitude or disappeared after an intracarotid injection of hypertonic saline solution (10 ml of 2000 mOsm/kg solution), we conclude that this c-wave enhancement by iodate is not the effect of the osmotic change.…”
Section: Discussionmentioning
confidence: 55%